Sexuality & Mental Health: Sexual Responses of Young Blind Females Experienci A Romantic Relationship - Fatimatuzzahra, Ana; Nursaniah, Sofi Septiani Julaeha; Qurrotullain, Aini; Rochyadi, Endang; Sunardi, Sunardi; Hasan, Herlina (Proceeding of International Conference on Special Education in South East Asia Region, 2024)
The study presented herein delves into the sexual responses of young blind females involved in romantic relationships. More speciﬁcally, it focuses on the four stages of sexual response—Excitement/Arousal Response, Plateau Response, Orgasm Response, and Resolution Response—within the context of mental health. The primary objective of this research endeavor is to garner insights into the navigation and response of these individuals to sexual experiences within the framework of romantic relationships, as well as to comprehend the impact of said experiences on their mental well-being. To achieve this objective, a qualitative exploratory approach was employed, with the participants being seven adolescent blind females ranging in age from 16 to 19 years old. It is noteworthy that these individuals were interviewed at a specialized school for the visually impaired in West Java. The ﬁndings unveiled that sensory experiences, communication with partners, and societal misconceptions signiﬁcantly inﬂuence the sexual response experiences of young Blind females, which in turn are intertwined with their mental well-being. This research aims to understand how young blind women's sexuality and mental health intersect in romantic relationships.